(untitled) (Journal of Economic Research & Business Administration, 2016)
In this article examined authors to the feature of management and organization of innovative activity in Kazakhstan, about development of realization industrially-innovative strategy in a country, to provide stability of economy on the first stage In the modern world innovative activity is examined as a major factor of providing of competitiveness and economy growing. Scientific and technical innovations determine the level of com- petitiveness of national commodities and all economy on the whole in the conditions of globalization of world economy